Scrap picking as smokescreen for criminal activities: The case of cross River North, Nigeria - Eneji, Rosemary Ine; E-C, Uzoh Esther; Ebagu, Tangban Egbe; Anam, Bassey Ekpenyong; Itita, Ede Victor (Edelweiss Applied Science and Technology, 2025)
Criminal activities arising from scrap-picking activities have become a recurring concern in many towns and cities in Cross River State of Nigeria, due to increasing demand for used or recyclable materials in the country. This study examined how scrap-picking contributes to incidences of crime in the state, focusing on trends and challenges. The study was carried out in Cross River State, where scrap pickers, scrap dealers, and security agents in Calabar South, Biase, and Bekwarra Local Government Areas were studied, in addition to community leaders and youths. One hundred and eight (108) persons participated in the study, which also involved focused group discussions and interviews. We found that scrap-picking has played a major role in the vandalization of public and private facilities in the state. Children less than 18 years of age were actively involved in scrap-picking activities, making them miss school, become psychologically stressed, and impairing their development. We suggest that community participation in addressing vandalism, metal theft, and child labor should be intensified. The interplay between scrap-picking and crime identified in this study should help law enforcement agencies and responsible stakeholders address some crime challenges and guide the development of targeted interventions to address criminal activities associated with scrap-picking.